Uji efektivitas ekstrak etanol air kelopak bunga Hibiscus sabdariffa linn terhadap profil lipid tikus hiperlipidemia - Ode Mahesa Putra; I Made Jawi; Bagus Komang Satriyasa (Intisari Sains Medis, 2019)
Introduction: Cardiovascular disease is still the biggest cause of death in the world. Many factors that play a role in the development of this disease, one of them is Hiperlipidemia. The situation can be handled using conventional medicines, but there are concerns about the side effects of conventional medicines. Hibiscus Sabdariffa L. (roselle) is rich in polyphenols, anthocyanins, flavonoids which can be used as drugs for the prevention of cardiovascular diseases that have biological activities such as antihypertensive, antimutagenic, chemopreventive, antioxidant, anticonvulsant, anxiogenic, CNS-depressant, serotoninergic activity, reducing damage from oxidative liver, anti-inflammatory and hypoglycemic activity. This study aims to evaluate the effects of roselle ethanol extract as a hypolipidemic agent.Method: This study used an experimental design, using wistar mouse divided into five groups: C1 received aquadest intervention, C2 (simvastatin 0.2g / kg / day), I1 (100mg / kg / day roselle extract), I2 (200 mg / kg / day roselle extract), and I3 (300 mg / kg / day roselle extract) mice was given hypercholesterol oil feed for two weeks preceeding drugs intervention, then intervention was given for eight weeks and analyzed on mouse lipid profile component.Result: There were significant differences in total cholesterol, triglyceride, LDL, and HDL values among the intervention groups (p = 0.000). The lowest total cholesterol belonging to the C2 group (117.83 ± 6.36) was followed by I3 (143.66 ± 11.75), the lowest triglyceride belonging to the C2 group (284.83 ± 7.46) was followed by I3 (306.84 ± 8.61), the lowest LDL was owned by the group C2 (104.50 ± 4.37), followed by I3 (120.50 ± 2.42), the highest HDL belonging to the C2 group (44.80 ± 3.16 followed by I3 group (38.02 ± 3.40).Conclusion: The ethanol extract at 300mg / kg / day gave better improvement of lipid profile rather than roselle ethanol extract 100mg / kg / day, 200 mg / kg / day, and aquadest control, but still not able to provide better improvement than simvastatin.